STUDI KITAB-KITAB KESAHIHAN MATAN HADIS - Syafe'i; Alma'arif; Taufik; Suheryeni; Syafe'i, Syafe'i (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines hadith compilations from the pre-Kutub al-Sittah period—such as Al-Muwaṭṭa’, Musnad al-Syāfi‘ī, and Musnad Aḥmad—to the six canonical collections of Kutub al-Sittah (Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, Jāmi‘ al-Tirmiżī, Sunan al-Nasā’ī, and Sunan Ibn Mājah) in order to understand the systematic development of hadith text (matan) verification. Using a qualitative method and library research approach, the study reveals that classical scholars did not assess the sanad alone but also examined the matan based on its consistency with the Qur’an and mutawātir Sunnah, rational coherence, internal consistency, and historical context. The findings affirm that matan criticism constitutes an integral and enduring part of the scientific methodology of hadith studies. This research recommends strengthening the study of matan authenticity through an interdisciplinary approach that integrates historical, linguistic, and social dimensions, as well as reinforcing hadith studies curricula in Islamic educational institutions to enable future scholars to interpret hadith both textually and contextually while preserving the authenticity of the Prophet’s teachings